Yellow Perch, Perca Flavescens, Growth and Survival on Different Feeds and in Low Salinity Environments - (:unkn) unknown (My University, 2020)
The development of effective culture techniques in the rearing of yellow perch (Perca flavescens) (Mitchill 1814) has multi-lateral benefits including enriching recreational resources, helping conservation efforts, as well as providing quality sea-food production. A myriad of challenges is yet to be remediated if yellow perch aquaculture is going to prosper. One of the challenges that hinders yellow perch aquaculture is the lacking supply of high-quality fingerlings. With current techniques employed by yellow perch hatcheries, the survival of yellow perch up to 30-day post hatch (DPH) age is typically less than 10%. Furthermore, larval culture has depended on imported dry feed developed for other species of fish, as well as live feed (artemia nauplii, rotifers, and even copepods), which may not be specific to yellow perch. Thus, it is critical to investigate new hatchery techniques and diets to increase larval survival during their early life stages. The overall goal of this research is to increase the yellow perch production efficiency by developing new culture techniques for yellow perch hatchery and fingerling production. Three experiments were completed in this study. The objective of the first experiment was to determine the best feeding practices for the yellow perch. For this, yellow perch larvae were fed artemia which had undergone a decapsulation process, artemia which had not, as well as two formulated dry diets. These consisted of a popular commercial larval fish feed and a lab formulated larval feed. The live feed was fed in combination with dry feed as well. The diets were fed from 16 DPH to 30 DPH. The results showed that live feed performed better than the dry feeds in larval fish survival (p The objective of this next study was to assess whether 5-ppt saltwater had any effects on yellow perch embryos, as well as larval growth and survival, if used as an alternative to formalin for pathogen control. The conditions during embryo incubation were: Freshwater with formalin, 5-ppt saltwater with formalin, and 5-ppt saltwater without formalin. The embryos were photographed daily during development and measured for endogenous nutrition depletion from 0 days post spawn (DPS) to 7 DPS. The results showed a significantly higher endogenous nutrition diminishment among treatments with formalin than the 5-ppt saltwater without formalin (p The third experiment determined if 5-ppt saltwater could enhance fingerlings previously grown solely in freshwater. Yellow perch fingerlings (192 DPH) were fed a high carbohydrate diet (25% wheat flour) containing 41% protein compared to a fishmeal-based diet containing 54% protein with no added carbohydrate. The feeding trial lasted for 8 weeks in a recirculating aquaculture system run with either freshwater or 5-ppt salinity water. The study showed no significant difference in growth between treatments reared at a 5-ppt low salinity and freshwater environment. The study did however find a significantly higher feed conversion ratio (FCR) in perch raised in saltwater as well as a higher hepatosomatic index (HSI). The protein efficiency ratio (PER) was higher in perch fed the wheat flour diet compared to those fed the fishmeal diet. These results conclude that more research into the optimal amount of carbohydrate inclusion in the yellow perch diet is needed, as well as the implementation of a low salinity environment.
Keywords: Carbohydrate; Embryo; Nutrition; Perca flavescens; Salinity; Yellow Perch